Leveraging the Domain of Work to Improve Migrant Health - Flynn, Michael A. (Int J Environ Res Public Health, 2017)
Work is a principal driver of current international migration, a primary social determinant of health, and a fundamental point of articulation between migrants and their host society. Efforts by international organizations to promote migrant health have traditionally focused on infectious diseases and access to healthcare, while international labor organizations have largely focused on issues of occupational health. The underutilization of the domain of work in addressing the health of migrants is truly a missed opportunity for influencing worker well-being and reducing societal economic burden. Understanding of the relationships among migration, work, and health would facilitate further integration of migrant health concerns into the policy agenda of governments and international agencies that work at the nexus of labor, health and development. The domain of work offers an opportunity to capitalize on the existing health and development infrastructure and leverage technical resources, programs and research to promote migrant health. It also provides the opportunity to advance migrant health through new and innovative approaches and partnerships.